English language for touristic purposes through a system of signposting with historical and cultural information in english and spanish for historical center of latacunga during the academic cicle april- august 2015 - Zumbana Mondragón, Daniela Estefanía (2016)
English is a rich source of knowledge, culture and tradition for the inhabitants of a locality that is linked to tourism. Then, this proposal formulated the following question; “Which are the advantages or disadvantages of using a system of interpretative signposting with Historic Information for the colonial building at Historic Center of Latacunga?”. In addition, the investigation has a general objective which propose a system of signposting with information in English and Spanish to facilitate a better comprehension of patrimonial signs. The project has been described through the use of inductive and deductive methods which were used to base the importance of English language for the touristic development and determine the process of design of interpretative signposting.